Distributed Fault Tolerant Architecture for Wireless Sensor Network - Mitra, Siba; Das, Ajanta (Informatica, 2017)
Smart applications use wireless sensor network for surveillance of any physical property of that area, to realize the vision of ambient intelligence. Since wireless sensor network is resource constrained and for unattended deployment scenario faults are quite trivial. Reliability and dependability of the network depends on in its fault detection, diagnosis and recovery techniques. Detecting faults in wireless sensor network is challenging and recovery of faulty nodes is very crucial task. In this research article, a distributed fault tolerant architecture is proposed. This paper also proposes fault recovery algorithms. Recovery actions are initiated based on fault diagnosis notification. The novelty of this paper is to perform recovery actions, using data checkpoints and state checkpoints of the node, in a distributed manner. Data checkpoint helps to recover the old data and the state checkpoint tells the previous trust degree of the node. Moreover, the result section explains even after replacement of a faulty node, the topology and connectivity between rests of the nodes are maintained in WSN.